HUBUNGAN KANDUNGAN AIR PADA LENSA KONTAK DENGAN KEJADIAN DRY EYE SYNDROME (DES) PADA MAHASISWA FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS KATOLIK INDONESIA ATMA JAYA - Levina Benita; Cisca Kuswidyati; Febie Chriestya (Atma Jaya Catholic University of Indonesia, 2019)
Introduction: Dry Eye Syndrome (DES) is a multifactorial disease of the eye characterized by loss of homeostasis from the tear film and is accompanied by ocular symptoms. One of many factors that can cause DES is the use of contact lenses. This research was conducted to determine the relationship of water content in contact lenses with the occurrence of DES. Methods: This research was conducted in 2019 with a cross-sectional study design with the Tear Break Up Time (TBUT) test, Schirmer test and questionnaire. The research respondents were students of Atma Jaya School of Medicine and Health Sciences (FKIK UAJ) whose eyes were examined as samples (n = 84). The water content of the respondent's contact lenses was obtained using a questionnaire. The inspection methods used to determine DES are TBUT test and Schirmer test. Data analysis using chi-square test with significance level of p <0.05. Results: The prevalence of DES obtained in students with a water content <50% is 25.9%, while the DES in students with a water content >50% is 25.5% . Conclusion: There is no significant relationship between water content in contact lenses with the occurrence of DES in FKIK UAJ students (p=0.963).